Clinical Features, Treatment, and Outcome of HIV-Associated Immune Thrombocytopenia in the HAART Era. (28th May 2012) - Ambler, Kimberley L. S.; Vickars, Linda M.; Leger, Chantal S.; Foltz, Lynda M.; Montaner, Julio S. G.; Harris, Marianne; Dias Lima, Viviane; Leitch, Heather A.
Abstract : The characteristics of HIV-associated ITP were documented prior to the HAART era, and the optimal treatment beyond HAART is unknown. We performed a review of patients with HIV-associated ITP and at least one platelet count <20 × 10 9 /L since January 1996. Of 5290 patients in the BC Centre for Excellence in HIV/AIDS database, 31 (0.6%) had an ITP diagnosis and platelet count <20 × 10 9 /L. Initial ITP treatment included IVIG, n = 12 ; steroids, n = 10 ; anti-RhD, n = 8 ; HAART, n = 3 . Sixteen patients achieved response and nine patients achieved complete response according to the International Working Group criteria. Median time to response was 14 days. Platelet response was not significantly associated with treatment received, but complete response was lower in patients with a history of injection drug use. Complications of ITP treatment occurred in two patients and there were four unrelated deaths. At a median followup of 48 months, 22 patients (71%) required secondary ITP treatment. This is to our knowledge the largest series of severe HIV-associated ITP reported in the HAART era. Although most patients achieved a safe platelet count with primary ITP treatment, nearly all required retreatment for ITP recurrence. New approaches to the treatment of severe ITP in this population are needed.